2007
DOI: 10.3803/jkes.2007.22.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics for 132 Patients with Adrenal Incidentaloma

Abstract: Background:Adrenal incidentaloma is an adrenal neoplasm frequently encountered in clinical practice for which detection rates have recently increased. We describe here the clinical characteristics of adrenal incidentalomas. Methods: A retrospective study was performed examining the age, sex, location, size, function, and the histological findings for 348 patients with an adrenal mass discovered incidentally on computed tomography (CT) undertaken for health examination or nonadrenal disease from August 2005 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Among the functional tumors, pheochromocytomas were the most frequently observed in our review, followed by subclinical Cushing's syndrome (6.0%), and aldosterone secreting adenoma (4.6%), closely resembling the results of another study done in Korea [25]. A study from a different country, however, reported differing results, that subclinical Cushing's syndrome was found at the highest incidence among functional masses [17].…”
Section: Discussionsupporting
confidence: 79%
“…Among the functional tumors, pheochromocytomas were the most frequently observed in our review, followed by subclinical Cushing's syndrome (6.0%), and aldosterone secreting adenoma (4.6%), closely resembling the results of another study done in Korea [25]. A study from a different country, however, reported differing results, that subclinical Cushing's syndrome was found at the highest incidence among functional masses [17].…”
Section: Discussionsupporting
confidence: 79%
“…In a previous Korean study, pheochromocytoma was seen at a much higher incidence, of up to 20%, of adrenal incidentalomas [13]. However, a separate Korean study and our data suggest that the incidence of pheochromocytoma was much lower, similar to that seen in Western data [11]. …”
Section: Discussionsupporting
confidence: 70%
“…Similar results were found in studies of Korean patients with adrenal incidentaloma. The incidence of functional adrenal tumors was reported to be 41.3% in Kim's study of 80 patients [ 10 ], but it was 13.6% to 18.7% in other studies [ 11 12 13 14 ]. There are several types of functional tumors: pheochromocytomas, with an average incidence of 6.2% (range, 2.1% to 20.0%); Cushing's syndrome (including symptom-free), with an average of 8.1% (range, 3.0% to 11.3%); and hyperaldosteronism, with an average of 3.9% (range, 1.5% to 10.0%).…”
Section: Epidemiology Of Adrenal Adenomamentioning
confidence: 99%